The Post-Divorce Maintenance (Maa’ta) for Muslim Women: Harmonizing Shariah Principles with Contemporary Legal Practices in Bangladesh and Modern World - Syeda Afroza Zerin; Asaduszaman Sohag; Md. Niamur Raquib (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Post-divorce maintenance (Maa’ta) for women in Islamic law is often a controversial topic, particularly regarding the interpretation and application of laws that vary across different countries. In Bangladesh, despite the Muslim-majority population, the legal framework governing women's post-divorce rights, specifically related to maintenance or maa'ta, remains unclear and has not been formally regulated. This study aims to analyze the application of Islamic law regarding post-divorce maintenance in Bangladesh's religious courts, as well as to explore the challenges faced by women in this context. The methodology used is a qualitative approach with a case study design, where data is collected through semi-structured interviews with judges, lawyers, and Islamic law experts, as well as observations of the judicial process in religious courts. In addition, documentation related to court decisions and legal regulations is also analyzed. The findings indicate that, although Islamic law recognizes women's right to post-divorce maintenance, its implementation in Bangladesh remains limited and uneven, with some cases not receiving any maintenance after the iddah period. This study contributes by identifying legal gaps and highlighting the need for reform to protect women's rights to post-divorce maintenance, while also providing insights for the development of a more responsive Islamic legal policy in Bangladesh to meet evolving social needs.